Genetic Base of Wheat Cultivars Recommended in Nepal - Rosyara, Umesh R; Joshi, Bal K (Nepal Agriculture Research Journal, 2010)
Plant breeding success is dependent, in part, upon the genetic diversity found within genetic resources. The genetic base of wheat (Triticum aestivum L.) cultivars recommended in Nepal is not well characterized. Therefore this study was carried out to quantify the genetic base of Nepalese wheat cultivars by coefficient of parentage (COP). Analysis of pedigree information was based on International Wheat Information System of the International Center for Maize and Wheat Improvement (CIMMYT), which consists of WCOP for calculation of COP and WPDEND for generating Mendelgram with contribution of ancestors to the cultivar if fully expanded. One hundred eighteen ancestors from 23 countries were identified in the pedigree of 24 recommended Nepalese cultivars. Of these, 32 ancestors contributed at least 1% each to the genetic base of Nepalese cultivars, with a total contribution of 79%. Ancestors originating from USA contributed 19.8% of the genes, India 11.2%, Japan 9.5%, Argentina 7.5%, Kenya 7.5% Australia 6.2%, Brazil 5.6%, Canada 5.5%, Italy 4.1% and remaining from other countries. At 30% similarity, 18 clusters were formed with largest cluster of five members. None of Nepalese landraces were traced in the pedigree of these cultivars. Relatively large amount of diversity in Nepalese cultivars exits based on their genetic background although small number of cultivars is recommended for cultivation. Key words: Coefficient of parentage; diversity; Triticum aestivum; wheat breeding DOI: 10.3126/narj.v6i0.3338 Nepal Agriculture Research Journal Vol.6 2005 pp.1-9